Unveiling the cloak of invisibility : why Black males are absent in STEM disciplines - Robins, Anthony G.; Knibbs, Locksley; Ingram, Ted N.; Weaver, Michael N., Jr; Hilton, Adriel A. (Emerald Publishing Limited : Information Age Publishing Inc., 2023)
"This book explores why Black men continue to be severely underrepresented in the STEM disciplines. It provides chapters that explore factors that lead to underrepresentation of Black males in STEM (e.g., societal traditions of what type of work is appropriate; the ruptured pipeline that leads to higher rates of attrition at every level of career development; barriers in science fields such as subtle and overt discrimination; and inequitable resources and opportunities). The premise of this volume is if Black males are to compete in an emerging global economy fueled by rapid innovation and marked by an astonishing pace of technological breakthroughs, they must be present. The book makes new contributions to the field. The collective of higher education professionals and change agents whom are tied to STEM bring cutting-edge thinking in how best to address the leaky STEM pipeline which has left the industry/workforce void of talented Black men. The volume promises timely, relevant and emergent scholarship and perspectives for STEM leadership, scholars and supporters. It provides promising practices (best practices) and recommendations in recruiting and retaining Black males in STEM disciplines and the competitive market place"-- Provided by publisher.
Keywords: African American men -- Education, Higher.; Science -- Study and teaching -- Social aspects -- United States.; African Americans in the professions.; Education -- Schools -- Levels -- Higher.; Higher education, tertiary education.; elektronické knihy; electronic books